Conserved metabolic steps for sporopollenin precursor formation in tobacco and rice. Issue 1 (7th January 2013) - Wang, Yanbing; Lin, Ying‐Chen; So, Joan; Du, Yegang; Lo, Clive
Abstract : The development of pollen wall with proper sporopollenin deposition is essential for pollen viability and male fertility in flowering plants. Sporopollenin is a complex biopolymer synthesized from fatty acid and phenolic derivatives. Recent investigations in Arabidopsis have identified a number of anther‐specific genes involved in the production of fatty‐acyl monomers potentially required for exine formation. The existence of ancient biochemical pathways for sporopollenin biosynthesis has been widely proposed but experimental evidence from plant species other than Arabidopsis is not extensively available. Here, we investigated the metabolic steps catalyzed by the anther‐specific acyl‐CoA synthetase (ACOS), polyketide synthase (PKS) and tetraketide α‐pyrone reductase (TKPR). Using fatty acids as starting substrates, sequential activities of heterologously expressed tobacco enzymes NtACOS1, NtPKS1 and NtTKPR1 resulted in the production of reduced tetraketide α‐pyrones. Transgenic RNA interference lines were then generated for the different tobacco genes which were demonstrated to be indispensable for normal pollen development and male fertility. Similarly, recombinant rice OsPKS1 and OsTKPR1 were shown to function as downstream enzymes of NtACOS1. In addition, insertion mutant lines for these rice genes displayed different levels of impaired pollen and seed formation. Taken together, reduced tetraketide α‐pyrones appear to represent common sporopollenin fatty‐acyl precursors essential for male fertility in taxonomically distinct plant species.